Gene emrC Associated with Resistance to Quaternary Ammonium Compounds Is Common among Listeria monocytogenes from Meat Products and Meat Processing Plants in Poland - Iwona Kawacka; Agnieszka Olejnik-Schmidt (Antibiotics, 2024)
(1) Background: L. monocytogenes is a food pathogen of great importance, characterized by a high mortality rate. Quaternary ammonium compounds (QACs), such as benzalkonium chloride (BC), are often used as disinfectants in food processing facilities. The effectiveness of disinfection procedures is crucial to food safety. (2) Methods: A collection of 153 isolates of L. monocytogenes from meat processing industry was analyzed for their sensitivity to BC using the agar diffusion method. Genes of interest were detected with PCR. (3) Results: Genes emrC, bcrABC, and qacH were found in 64 (41.8%), 6 (3.9%), and 1 isolate (0.7%), respectively, and 79 isolates (51.6%) were classified as having reduced sensitivity to BC. A strong correlation between carrying QACs resistance-related genes and phenotype was found (p-value < 0.0001). Among 51 isolates originating from bacon (collected over 13 months), 48 had the emrC gene, which could explain their persistent presence in a processing facility. Isolates with the ilsA gene (from LIPI-3) were significantly (p-value 0.006) less likely to carry QACs resistance-related genes. (4) Conclusions: Reduced sensitivity to QACs is common among L. monocytogenes from the meat processing industry. Persistent presence of these bacteria in a processing facility is presumably caused by emrC-induced QACs resistance.